Riset Pasar Produk Kecap Coconut Aminos : (Studi Kasus Coconut Aminos “Gulapa” PT. Berkat Petani Indonesia ) - Dharmawan, Budi; Widyarini, Indah; Satriani, Ratna; Sudarmadji, Arief; Novia, Rifki Andi; Sakhidin; Karseno; Sunendar (Universitas Medan Area, 2025)
Consumer awareness of a healthy lifestyle is driving an increase on demand for food products that are low in sodium, gluten-free, and made from natural ingredients. Coconut aminos with the brand